Fosfitos no manejo da antracnose da soja - Silva Júnior, Manoel Batista da (2017)
Temperature and inoculum density may directly affect the manifestation of anthracnose in soybean. Detection of the pathogen in seeds is paramount for healthy crops. The qPCR technique presents precision for this purpose. Chemical control by both seed treatment and spray treatment offers risks. Thus phosphites are a promising, viable and sustainable alternative for this purpose. These products can act by nutrition and induction of resistance in the host and direct toxicity to the pathogen. The objective of this study was to evaluate the effect of temperature and inoculum density on anthracnose severity, to detect the pathogen by qPCR in seeds and to evaluate phosphites in the management of the disease in seeds and pods. In the first study the effect of temperature on the mycelial growth of C. truncatum isolates, effect of inoculum density on the severity of the anthracnose in seeds and specific primers for the detection of the pathogen by PCR was evaluated. There was a significant difference in the growth of the isolates as a function of temperature. There was significant effect of the inoculum density on the germination and sanity of the soybean meal. The LAPS473 isolate was the most severe to the seeds. The primers designed were specific in the detection of C. truncatum and there was amplification until the dilution of 20 fg. In the second test the seeds were inoculated with the most severe isolate and treated with Cu, K, Mn and Zn phosphites. Vigor, germination and sanity tests were performed and the mode of action of the phosphites was evaluated by induction of resistance and direct toxicity. Mn and Zn phosphites were effective in the management of the disease, increasing germination and vigor and reducing the incidence of the pathogen. Mn phosphite promoted increases in CAT and POX activity and increase in lignin content. Zinc phosphite increased POX activity. Both products were toxic to C. truncatum. In the third trial the same phosphites were evaluated in the management of anthracnose in soybean pods, in the control of the transmission of the pathogen from pods to the seeds and in the activation of the defense mechanisms. The inoculation was performed by spraying the inoculum suspension in R4. The application of the products was carried out in V4, R1 and R3 with volume of application of 200 L.ha-1 and pressure of 40 psi. Five evaluations of the disease were performed and the AACPS and control of each treatment were calculated. All the products reduced the severity of the anthracnose in the pods and the transmission of the pathogen from the pods to the seeds, but the phosphites of Cu, Mn and K promoted greater control. Potassium phosphite increased the lignin content. Mn phosphite increased CAT activity and lignin content. Copper phosphite increased CAT and POX activity.